Systematic review of sexual risk among pregnant and mothering teens in the USA: pregnancy as an opportunity for integrated prevention of STD and repeat pregnancy. - Meade, Christina S; Ickovics, Jeannette R (Social science & medicine (1982), 2005)
Behaviors that lead to teen pregnancy also place young women at risk for STDs and repeat pregnancy. Compared to the broad literature on adolescent sexual risk behavior, our understanding of sexual risk in pregnant/mothering teens lags far behind. Primary objectives of this systematic review (1981-2003) of pregnant/mothering teens were to: (1) document rates of STD, repeat pregnancy, condom use, and contraception; (2) identify correlates of these biological and behavioral outcomes; (3) review sexual risk reduction interventions; and (4) discuss directions for future research and implications for clinical care. Fifty-one studies met inclusion criteria. Rates of STD and repeat pregnancy were high, with the majority of teens engaging in unprotected sex during and after pregnancy. An Ecological Model of Sexual Risk, based on Bronfenbrenner's (1989) Ecological Systems Theory, was proposed to organize findings on correlates of sexual risk. Improvements in research, including integration of outcomes and risk factors, stronger methodologies, and standardized assessments, are essential. Results suggest that teen pregnancy is a marker for future sexual risk behavior and adverse outcomes, and that pregnant/mothering teens need hybrid interventions promoting dual use of condoms and hormonal contraception. Pregnancy may provide a critical "window of opportunity" for sexual risk reduction.
Keywords: Adolescent; Adolescent Behavior; Contraception Behavior; Female; Humans; Pregnancy; Pregnancy in Adolescence; Risk-Taking; Sexual Behavior; Sexually Transmitted Diseases; United States